1991
DOI: 10.1259/0007-1285-64-757-5
|View full text |Cite
|
Sign up to set email alerts
|

Complications in percutaneous transluminal angioplasty: relationships with patient age

Abstract: Five hundred consecutive attempted lower limb angioplasties for ischaemic disease (370 patients, mean age 65.6 years, range 33-91 years) were reviewed. Significant complications occurred in 44 cases (8.8%). Nine patients (1.8%) underwent emergency surgery related to a complication. A further 12 patients (2.4%) underwent elective surgery related to a complication. In addition, four patients died within 30 days of the procedure; one following surgery performed because of a complication of angioplasty, one follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…We suggest that this is because the majority of intraluminal angioplasties were performed for stenoses whereas the majority of subintimal angioplasties were performed for occlusions. 16 Overall, in the present series, 14% of limbs suffered an early complication, this is very much in keeping with published complication rates. It is important to note, however, that the majority of these complications (97%) were managed by endovascular techniques with surgery being required in only 0.5% of all patients.…”
Section: Discussionsupporting
confidence: 91%
“…We suggest that this is because the majority of intraluminal angioplasties were performed for stenoses whereas the majority of subintimal angioplasties were performed for occlusions. 16 Overall, in the present series, 14% of limbs suffered an early complication, this is very much in keeping with published complication rates. It is important to note, however, that the majority of these complications (97%) were managed by endovascular techniques with surgery being required in only 0.5% of all patients.…”
Section: Discussionsupporting
confidence: 91%
“…A previous multivariate analysis demonstrated an odds ratio for critical ischemia of 2.5 (95% CI 1.4 to 4.7) in predicting morbidity and 4.7 (95% CI 1.2 to 17.9) in predicting 30-day mortality rates. 6 Other studies have found indication and age to be significant risk factors for complications, z°, 21 The multivariate analysis presented here supports the hypothesis that the presence of critical ischemia and the patient's age significantly increase the risk of complications associated with angioplasty. The odds ratios for the presence of occlusion, hypertension, and diabetes mellitus indicate that these may be additional risk factors for complications; however, the sample size is too small to demonstrate statistical significance with control for indication and age.…”
Section: Discussionsupporting
confidence: 80%
“…Although the complication rate of PTA is low, nonetheless a small percentage (2%) of patients will require surgery to correct complications. 16 There are no complications of exercise training, nor does it compromise subsequent PTA or surgery should they be necessary. Exercise training has the additional merit of promoting a generalised feeling of well-being.…”
Section: Discussionmentioning
confidence: 99%